Isolation and Identification of Microorganisms Found in Roasted Dog Meat Within Wukari Metropolis, North-East Nigeria - Brown, Samuel Tamunoiyowuna Cockeye; Mohammed, Usman Ikrimah; Onyemaechi, Eze Emmanuel; Sunday, Danya (African Journal of Clinical Medicine and Pharmacy Research, 2025)
This study evaluated the microbiological quality of roasted dog meat sold within Wukari Metropolis, Taraba State, to determine its safety for human consumption. Eight samples of roasted dog meat were collected and analyzed for Total Viable Count (TVC), coliform count, and bacterial identification using standard biochemical methods. The findings revealed varying levels of microbial contamination, with several samples exceeding the acceptable microbial load limits established by the World Health Organization (WHO) and the Food and Agriculture Organization (FAO). Notably, the highest TVC values were observed in samples YM2 (3.00 × 10⁶ cfu/g), YM1 (1.56 × 10⁶ cfu/g), and AS1 (1.20 × 10⁶ cfu/g), indicating significant bacterial presence. Coliform counts confirmed fecal contamination, with Escherichia coli identified in multiple samples. Biochemical analysis further revealed the presence of Salmonella spp. (20%), E. coli (13.33%), Staphylococcus aureus (13.33%), Pseudomonas aeruginosa (6.67%), Chromobacterium violaceum (13.33%), and Neisseria mucosa (6.67%). The identification of these pathogenic organisms underscores serious public health concerns linked to inadequate hygiene, poor handling practices, and environmental contamination. The study emphasizes the urgent need for stricter food safety regulations, vendor hygiene training, and improved meat handling protocols. Additionally, public health awareness campaigns are recommended to educate both vendors and consumers on the risks associated with consuming improperly handled street-vended meat.